Perioperative atezolizumab plus fluorouracil, leucovorin, oxaliplatin, and docetaxel for resectable esophagogastric cancer: interim results from the randomized, multicenter, phase II/III DANTE/IKF-s633 trial - Lorenzen, Sylvie; Götze, Thorsten Oliver; Thuss-Patience, Peter; Biebl, Matthias; Homann, Nils; Schenk, Michael; Lindig, Udo; Heuer, Vera; Kretzschmar, Albrecht; Goekkurt, Eray; Haag, Georg Martin; Riera-Knorrenschild, Jorge; et al. (Journal of clinical oncology, 2024)
Purpose - This trial evaluates the addition of the PD-L1 antibody atezolizumab (ATZ) to standard-of-care fluorouracil, leucovorin, oxaliplatin, and docetaxel (FLOT) as a perioperative treatment for patients with resectable esophagogastric adenocarcinoma (EGA). - Methods - DANTE started as multicenter, randomized phase II trial, which was subsequently converted to a phase III trial. Here, we present the results of the phase II proportion, focusing on surgical pathology and safety outcomes on an exploratory basis. Patients with resectable EGA (≥cT2 or cN+) were assigned to either four preoperative and postoperative cycles of FLOT combined with ATZ, followed by eight cycles of ATZ maintenance (arm A) or FLOT alone (arm B). - Results - Two hundred ninety-five patients were randomly assigned (A, 146; B, 149) with balanced baseline characteristics between arms. Twenty-three patients (8%) had tumors with microsatellite instability (MSI), and 58% patients had tumors with a PD-L1 combined positive score (CPS) of ≥1. Surgical morbidity (A, 45%; B, 42%) and 60-day mortality (A, 3%; B, 2%) were comparable between arms. Downstaging favored arm A versus arm B (ypT0, 23% v 15% [one-sided P = .044]; ypT0-T2, 61% v 48% [one-sided P = .015]; ypN0, 68% v 54% [one-sided P = .012]). Histopathologic complete regression rates (pathologic complete response or TRG1a) were higher after FLOT plus ATZ (A, 24%; B, 15%; one-sided P = .032), and the difference was more pronounced in the PD-L1 CPS ≥10 (A, 33%; B, 12%) and MSI (A, 63%; B, 27%) subpopulations. Complete margin-free (R0) resection rates were relatively high in both arms (A, 96%; B, 95%). The incidence and severity of adverse events were similar in both groups. - Conclusion - Within the limitations of the exploratory nature of the data, the addition of ATZ to perioperative FLOT is safe and improved postoperative stage and histopathologic regression.